One million hectares world wide - Varietal change in potatoes and the contribution of the International Potato Center - International Potato Center (2009)
Over 1 million hectares are planted worldwide with potato varieties bred by or obtained through the International Potato Center (known by its Spanish acronym CIP). According to a 2007 survey of 23 countries in Asia, Africa, and Latin America, the area planted with CIP-related material in those countries has increased from 6,4 percent to 13.1 percent in the last decade. This important milestone has come more than ten years earlier than was predicted in the best case scenario envisioned in 1997 and represents a 150 percent increase in area covered. In terms returns on investment in CIP breeding, the current adoption area implies a rate of return of approximately 20 percent per one dollar invested, and a net present value of discounted net benefits of more than USS121 million.